Darwins øje: En undersøgelse af øjet og blikket i J.P. Jacobsens Niels Lyhne - Hedin, Gry (Danske Studier, 2024)
It is the aim of this article to investigate the relationship between Jens Peter Jacobsen’s literary output and Darwinism from a new angle. The description of eyes and perception in the novel Niels Lyhne (1880) will be discussed in relation to the changes in this field that Darwin facilitated together with the German physiologist Hermann von Helmholtz. It is a central argument that our sensational relationship with the world is historically grounded, and that Niels Lyhne is strongly situated in the findings of the natural sciences of its day. It will be argued that Jacobsen in the novel investigates the epistemological consequences of the changes in the understanding of perception, and that he emphasizes the limitations in the individual’s access to knowledge of itself and the surrounding world.